An autoethnographic inquiry into the emergence of new forms and ways of organizing - Turcan, Romeo V. (Communication & Language at Work, 2020)
This paper employs analytic autoethnography within a previous life in an organization and within social science to explore the emergence of new forms and ways of organizing in a new venture that was launched as a branch in an emerging market by an international non-for-profit organization. It responds to extant scarcity of knowledge about internal organization of entrepreneurial ventures as most of research about internal organization of firms comes from the research on large established organizations. In the early stage of new venture emergence, entrepreneurs shall be aware of the interplay between: understanding the new venture socio-politically and cognitively through unsophisticated uncertainty; timing of acquiring socio-political and cognitive legitimacy through legitimation temporaling; shared and non-shared understanding of the value (problem) of the new venture through disguised and true value theorizing; dependent and independent organization through diversifying funding sources; and headquarters and branch visions and missions through dominant logic crisis.